Rozmywanie granic: Geopoetyka węgierskiej trylogii Krzysztofa Vargi - Janiec-Nyitrai, Agnieszka (Slavia Centralis, 2020)
One of the most significant features of spatial categories that can be seen in the Hungarian trilogy written by Krzysztof Varga is blurring the boundaries – what appears to be central is depressingly peripheral; what is indicated as irrelevant suddenly grows to the level of the central and important. The alien is intertwined with the familiar, places and things that were originally sacred are devoid of these qualities, and what appears to be distant suddenly gains the rank of contemporary and close. During the analysis, we refer to the category of "body memory" (Thomas Fuchs) and the article also highlights an interesting point of view that Varga presents in his prose – he combines different perspectives of looking at the Hungarian territory.